Diseño de un banco experimental para medición de pérdida de transmisión acústica (2017)
The present project propounds the design and construction of a device of tests for the measurement of the loss of acoustic transmission, parameter used in the evaluation of the efficiency of devices of attenuation of the sound. For this, it began with the study of the different experimental methodologies used to compare the efficiency in silencers and their typology. Afterwards, a selection was made of the parameter of greatest recognition in the literature, the transmission loss and the alternatives used for its evaluation are evaluated. The selection of this alternative and the basic construction parameters were performed according to the ASTM E2611-09 standard that describes the appropriate measurement procedure.